Nationwide survey of patients in Japan with Bickerstaff brainstem encephalitis: epidemiological and clinical characteristics. Issue 12 (31st July 2012) - Koga, Michiaki; Kusunoki, Susumu; Kaida, Kenichi; Uehara, Ritei; Nakamura, Yosikazu; Kohriyama, Tatsuo; Kanda, Takashi
Abstract : Backgroud: Information regarding the epidemiological background of Bickerstaff brainstem encephalitis (BBE) is limited. Methods: We conducted a nationwide survey of BBE in the Japanese population in two steps: the first aimed to identify patients with brainstem encephalitis for the specified 3 year period and the second to evaluate whether the clinical picture met our diagnostic criteria for BBE. Results: The number of patients with brainstem encephalitis was estimated as 704 (95% CI 478 to 930) over the 3 years. The annual onset of BBE was roughly estimated as 100 cases, which accounted for 43% of brainstem encephalitis. BBE was slightly male predominant and often young onset. Among brainstem encephalitis patients, BBE was characterised by antecedent infectious symptoms, oropharyngeal palsy and sensory disturbance at the distal extremities with absent or decreased tendon reflexes, in addition to a triad of symptoms (external ophthalmoplegia, ataxia and impaired level of consciousness) and shorter duration to the peak, with good outcome. Anti-GQ1b antibodies were present in 75% of cases. Several BBE patients with atypical clinical features or without anti-GQ1b antibodies were also identified. These cases often had marked CSF pleocytosis, abnormal brain MRI findings and a longer duration to peak symptoms, sometimes with considerable residual deficits. Conclusions: BBE is a rare disorder but accounts for a major proportion of brainstem encephalitis. BBE consists of typical and atypical cases. Typical BBE has similar neurological and serological features to Fisher syndrome and shows good recovery whereas atypical BBE is characterised by delayed recovery, negative anti-GQ1b antibodies, and abnormal CSF and brain MRI findings with other possible pathogeneses.